Design of Supply Chain Management (SCM) performance measurement model using SCOR and Analytical Hierarchy Process (AHP): A case study at PT. Circle Pro Group (Central Java-Klaten) - Ibnu Nafis Al Khawarizmi; Narto Narto; Suparno Suparno (Priviet Social Sciences Journal, 2026)
This study aims to design a performance measurement model for Supply Chain Management (SCM) at PT Circle Pro Group, Klaten, Central Java, using the Supply Chain Operations Reference (SCOR) model and Analytical Hierarchy Process (AHP). The PT Circle Pro Group has not implemented any SCM performance measurement system, resulting in unclear performance levels and difficulties in identifying improvement priorities. The SCOR model was used to structure SCM activities into Plan, Source, Make, Deliver, and Return, whereas AHP was applied to determine the weight and priority of performance indicators. A total of 17 validated indicators were developed based on the SCOR processes and company conditions. The measurement results indicated an SCM performance score of 91.47, which was categorized as above average. However, several indicators scored below 90, particularly forecast accuracy, raw material planning, and supplier delivery punctuality. Recommendations for improvement include strengthening forecasting processes, optimizing procurement planning, and enhancing supplier performance evaluation. This study produces a structured SCM performance measurement model tailored for PT Circle Pro Group, enabling continuous evaluation and improvement. The model can be adapted by other service-based companies with similar operational characteristics.